Partners in crime - Harrington, Kim, 1974- (Harrington, Kim, 1974- Sleuth or dare ;, 2012)
"When best friends Darcy and Norah have to create a fake business for a school assignment, they come up with a great idea: a detective agency! Darcy loves mysteries, and Norah likes helping people, so it's a perfect fit. But then their pretend agency gets a real case. Someone is missing, and it's up to Darcy and Norah to take on the search. Unfortunately, there's someone else out there who doesn't want the two detectives stirring up any trouble. . . .With the help of hidden clues, spy gadgets, and trusted friends, can Darcy and Norah crack the case in time?" --P. [4] of cover.